2014
DOI: 10.1128/jvi.02789-13
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection, TLR3 Ligands, and Proinflammatory Cytokines Induce CD161 Ligand LLT1 Expression on the Respiratory Epithelium

Abstract: During respiratory-virus infection, excessive lymphocyte activation can cause pathology both in acute infection and in exacerbations of chronic respiratory diseases. The costimulatory molecule CD161 is expressed on lymphocyte subsets implicated in promoting respiratory inflammation, including Th2, Th17, mucosally associated invariant T (MAIT) cells, and type 2 innate lymphoid cells. We asked whether the CD161 ligand LLT1 could be expressed on respiratory epithelial cells following respiratory-virus infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
3
30
1
Order By: Relevance
“…Most viruses produce dsRNA at some point during their replication. In mammalian cells, dsRNA is a potent antigen recognized by sensors such as Toll-like receptor (TLR) 3, through which dsRNA can trigger the transcription-based antiviral interferon response (57,58). We found that stimulating endothelial cells with the dsRNA substrate poly(A:U), as well as with the synthetic viral dsRNA analog poly(I:C), increased the secretion of both RNase 1 and BRB significantly, whereas treatment with ssRNA or DNA did not.…”
Section: Discussionmentioning
confidence: 99%
“…Most viruses produce dsRNA at some point during their replication. In mammalian cells, dsRNA is a potent antigen recognized by sensors such as Toll-like receptor (TLR) 3, through which dsRNA can trigger the transcription-based antiviral interferon response (57,58). We found that stimulating endothelial cells with the dsRNA substrate poly(A:U), as well as with the synthetic viral dsRNA analog poly(I:C), increased the secretion of both RNase 1 and BRB significantly, whereas treatment with ssRNA or DNA did not.…”
Section: Discussionmentioning
confidence: 99%
“…LLT1 is not expressed by resting cells but is upregulated on the surface of various leukocytes upon activation [22,23]. It is also induced in epithelial cells in the lung following RSV infection or activation with proinflammatory cytokines or TLR3 ligands [24]. NKR-P1A has a clear inhibitory effect on human NK-cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…H. influenzae expresses the riboflavin biosynthetic pathway from which the MAIT-cell ligands are derived (30). The costimulatory molecule CD161 is a key expression marker for MAIT cells, which can recognize the ligand lectin-like transcript 1 (LLT1) expressed by respiratory epithelial cells in response to infection and proinflammatory cytokines (48). H. influenzae can invade the lung tissue (49,50) and enter respiratory epithelial cells and macrophages in chronic bronchitis (6)(7)(8)51).…”
Section: Cd161mentioning
confidence: 99%